Comparison between Accelerometer and Laser Vibrometer to Measure Traffic Excited Vibrations on Bridges - G. Rossi; R. Marsili; V. Gusella; M. Gioffrè (Shock and Vibration)
The use of accelerometer based measurement techniques for evaluating bridge forced vibrations or to perform bridge modal analysis is well established. It is well known to all researchers who have experience in vibration measurements that values of acceleration amplitude can be very low at low frequencies and that a limitation to the use of accelerometer can be due to the threshold parameter of this kind of transducer. Under this conditions the measurement of displacement seems more appropriate. On the other hand laser vibrometer systems detect relative displacements as opposed to the absolute measures of accelerometers. Vibrations have been measured simultaneously by a typical accelerometer for civil structures and by a laser vibrometer equipped with a fringe counter board in terms of velocity and displacements. The accelerations calculated from the laser vibrometer signals and the one directly measured by the accelerometer has been compared.